Job evaluation : a practical guide for managers - British Institute of Management (London : Management Publications Ltd. for the British Institute of Management, 1970)
This book is for professionals who want to add job evaluation to their management skills.
First ed. published in 1952 under title: Job evaluation: a practical guide.
Includes bibliographical references.
ucj 16/01/2019
Loans
Keywords: Job evaluation; Wages